Motion sickness and rigid body motion of a polar supply and research vessel on voyages to Antarctica and the Southern Ocean - Boulle, Brendan Guy (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.